Border humanitarians : gendered order and insecurity on the Thai-Burmese frontier - Saltsman, Adam P. (Syracuse studies in geography., 2022)
"Following the stories of exiled Burmese activists in Thailand who struggle to end gender violence among refugees, Border Humanitarians offers a critical lens to understand the politics of local and global human rights and aid work in contexts of displacement and mobility"--